Survey of Salary and Job Satisfaction of Transplant Nephrologists in the United States. Issue 9 (September 2022) - Singh, Neeraj; Doshi, Mona D.; Schold, Jesse D.; Preczewski, Luke; Klein, Christina; Akalin, Enver; Leca, Nicolae; Nicoll, Kimberly; Pesavento, Todd; Dadhania, Darshana M.; Friedewald, John; Samaniego-Picota, Milagros; et al.
Visual Abstract: Abstract : Background and objectives: There are no standardized benchmarks to measure productivity and compensation of transplant nephrologists in the United States, and consequently, criteria set for general nephrologists are often used. Design, setting, participants, & measurements: A web-based survey was sent to 809 nephrologists who were members of the American Society of Transplantation to gather data on measures of productivity, compensation, and job satisfaction. Factors associated with higher total compensation and job satisfaction were examined. Results: Of 365 respondents, 260 were actively practicing in the United States and provided data on compensation. Clinical productivity was assessed variably, and although 194 (76%) had their work relative value units (wRVUs) reported to them, only 107 (44%) had an established RVU target. Two hundred thirty-four respondents (90%) had fixed base compensation, and 172 (66%) received a bonus on the basis of clinical workload (68%), academic productivity (31%), service (32%), and/or teaching responsibility (31%). Only 127 respondents (49%) filled out time studies, and 92 (35%) received some compensation for nonbillable transplant activity. Mean total compensation (base salary and bonus) was $274, 460±$91, 509. The unadjusted mean total compensation was higher with older age and was higher for men; Hispanic and White respondents; adult care transplant nephrologists; residents of the western United States; US medical school graduates; nonuniversity hospital employees; and those with an administrative title, higher academic rank, and a higher number of years in practice. Two hundred and nine respondents (80%) thought their compensation was unfair, and 180 (70%) lacked a clear understanding of how they were compensated. One hundred forty-five respondents (55%) reported being satisfied or highly satisfied with their job. Job satisfaction was greater among those with higher amounts of compensation and US medical school graduates. Conclusions: We report significant heterogeneity in the assessment of productivity and compensation for transplant nephrologists and the association of compensation with job satisfaction.